AN ANALYSIS OF STUDENTS' SPEAKING PROBLEMS IN DIALOG AT MA'HAD AL-JAMI'AH - Sopiah, Siti; Indrasari, Nunun (Journal of Linguistics and Social Sciences, 2025)
This study investigates the speaking problems and communication strategies of fourth-semester students living at Ma’had al-Jami’ah, UIN Raden Intan Lampung. A mixed-method design was applied, combining quantitative data from questionnaires and qualitative data from interviews and documentation. The findings show that students face several challenges in speaking English, such as inhibition, lack of ideas, reliance on the mother tongue, and hesitation to participate. The most dominant issue was inhibition, with many students afraid of making mistakes, criticism, or being the center of attention. Lack of vocabulary and limited confidence further hindered their speaking performance. Despite these difficulties, students employed various strategies, including paraphrasing, approximation, simplifying messages, creating new words, using gestures, and seeking help from peers or teachers. The study concludes that speaking problems are not only linguistic but also psychological, requiring attention to both aspects in classroom practice. The results contribute to theoretical discussions on language learning in Islamic boarding school contexts and provide practical insights for tutors and curriculum developers to improve speaking programs.